Diagnostic of Helicobacter pylori infection. (September 2016) - Mégraud, Francis; Floch, Pauline; Labenz, Joachim; Lehours, Philippe
Abstract: There is progress in endoscopy techniques. While it is not yet possible to detect Helicobacter pylori directly in the stomach, it becomes easier to detect the mucosal changes induced by the bacteria. Some small changes can also increase the sensitivity of the invasive tests, for example culture or histology, but the wide use of proton‐pump inhibitors has a negative impact on these tests. Only molecular methods are able to detect a limited load of bacteria, especially by using real‐time PCR but also with new methods, for example dual‐priming oligonucleotide‐based PCR, loop‐medicated isothermal amplification, droplet‐digital PCR or a multiple genetic analysis system. Among the noninvasive tests, urea breath test remains a test of major interest, while there are attempts to develop an ammonia breath test and other nanosensor devices. A new antigen stool test, a chemoluminescence immunoassay using the LIAISON apparatus has also been tested for the first time with success. Despite its limitations, serology remains the most popular test to detect H. pylori antibodies. It also allows pepsinogen dosage which is of interest for detecting atrophy.